Khuruj in the Nidzamuddin Tabligh Jamaah: Implementation and religious implications in Bandung - Bukhori, Bukhori; Jamaluddin, Adon Nasurullah; Zuldin, Muhamad (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2025)
This study investigates the implementation of khuruj within the Nidzamuddin faction of the Tablighi Jamaat in Bandung, Indonesia, and examines its implications for the religious behavior of its members. Using a descriptive qualitative approach with a case study method, the research collected data through in-depth interviews, participant observation, and document analysis. The analysis is framed through Max Weber’s theory of social action, which helps interpret khuruj as a form of meaningful and multidimensional religious engagement. The findings show that khuruj is not a mechanical or purely traditional ritual. It is a dynamic process shaped by affective experiences, rational calculations, and deeply held spiritual values. The practice contributes to personal religious transformation, strengthens consistency in worship, and fosters a sense of communal responsibility in religious outreach. The study also explores how internal organizational tensions, particularly the split between the Nidzamuddin and Syura Alami factions, reshaped the movement’s social structure and emphasized the role of value-based cohesion. This research contributes to the sociology of religion by showing how informal, experiential religious practices can influence identity formation and offer meaningful alternatives to formal religious education.